تحضير ودراسة الأغشية الرقيقة لكبريتيد الكادميوم ( CdS) المرسب بطريقة الحمام الكيميائي ( CBD) - بيسي, عبد الكريم; نغموش ,نصر أحمد (جامعة الوادي university of eloued, 2024)
تم في هذا العمل دراسة مدى تأثير درجة الحرارة على الخواص البنيوية والضوئية للأغشية الرقيقة لكبريتيد الكادميوم المرسبة وفق طريقة الحمام الكيميائي على شرائح زجاجية حيث تم تحضير هاته الأغشية انطلاقا من كبريتات الكادميوم كمصدر لـ Cd+2و الثوريا كمصدر للكبريتيدS-2 مع استعمال الأمونياك كمعقد للتفاعل. أظهرت نتائج انعراج الأشعة السينية أن الأغشية المحضرة ذات بنية مكعبة والاتجاه المفضل (111). أوضحت نتائج uv-vis أن الأغشية المحضرة ذات نفاذية تقارب 70%. أما الفجوة الطاقية المتحصل عليها تتراوح بين eV (2.21-2.32). In this work, the effect of the temperature on the structural and optical properties of cadmium sulfide thin films deposited by chemical bath method onto glass slides was studied. The cadmium sulfate and thoria were used as source of Cd2+ and S2- respectively. Ammonia was used as a complex agent for the reaction. The films properties have been investigated as a function of bath temperature. Structural properties of the obtained films were studied by X-ray diffraction analysis. The main obtained results that deposited CdS thin films have a cubic phase structure and a preferred orientation in the (111) plane. The structural parameters such as crystallite size have been evaluated. The transmission spectra, recorded in the UV visible range reveal a relatively high transmission coefficient (70%) in the obtained films. The transmittance data analysis indicates that the optical band gap is closely related to the deposition conditions, a direct band gap ranging from 2.21 eV to 2.32 eV was deduced. Keywords: thin films, structural and optical properties, cadmium sulfide, chemical bath, X-ray diffraction, transmittance.
مدكرة ماستر فيزياء
Keywords: غشية رقيقة; الخواص البنيوية; الخواص الضوئية; كبريتيد الكادميوم الحمام الكيميائي; انعراج الأشعة السينية; النفاذية; فجوة الطاقة; thin films; structural and optical properties; cadmium sulfide; chemical bath; X-ray diffraction; transmittance.